Islamic Economics in the Middle of Civilization Transition - Mohammad Ghozali; Resi Handayani; Wahyudi Bakri (JOURNAL OF SHARIA ECONOMICS, 2021)
The existence of an economic system of capitalism, an economic system of socialism, and an economic system of sharia are a response to problems regarding the economy as well as an answer to removing people from the obscurity of the existing economic system. It’s hoped that these systems will be the key to the economic success of a society. But there are always advantages and disadvantages to every existing system. The economic system of capitalism is an economic system hi which investors or owners of capital are the movers and rulers. Meanwhile, the economic system of socialism is a system hi which the government is the main control, this system ignores the position of the individual, everything is regulated by the ruler and no one has the right other than the ruler. The considerations positives and negatives of each system have created a sharia economic system where this system has every positive side of the capitalist and socialist economic system but ignores the shortcomings or negative sides of the two systems. This paper discussed how the economic system of capitalism, the economic system of socialism, the Islamic economic system, and the relationship between them. The method used in this writing was library research, in which the authors used various secondary data from books, article, and many more. The results showed that it is clear that there are far differences between the conventional economic system and the Islamic economic system, the conventional economic system includes the economic system of capitalism and the economic system of socialism.